POSTMODERN DECONSTRUCTIONS OF THE BILDUNGSROMAN IN BRITISH LITERATURE - Muradova Yulduz Abdihamidovna (Modern American Journals, 2025)
This article investigates how postmodern British literature deconstructs the traditional Bildungsroman, or coming-of-age narrative. It explores how postmodern techniques—fragmentation, metafiction, intertextuality, and irony—challenge the linear, coherent model of identity formation central to classical Bildungsromane. Focusing on texts such as Julian Barnes’ The Sense of an Ending, Jeanette Winterson’s Oranges Are Not the Only Fruit, and Hanif Kureishi’s The Buddha of Suburbia, the article examines how British authors destabilize the genre to reflect pluralism, disillusionment, and the postmodern self. Ultimately, it argues that postmodern deconstructions of the Bildungsroman reveal new modes of character development that are fractured, multi-voiced, and perpetually in process.
Keywords: Bildungsroman, postmodernism, British literature, identity, metafiction, fragmentation, coming-of-age